(untitled) (Orthodontic Journal of Nepal, 2014)
Objective: To compare the craniofacial features of male and female Chinese samples with Angle Class II Division 1 malocclusion. Materials & Method: The cephalometric radiographs were obtained from 39 Chinese subjects (mean age17.18 ± 7.1 years) with Angle Class II Division 1 malocclusion. Ten skeletal, nine dental and three soft tissue variables were investigated. Result: The craniofacial features between Chinese genders showed statistical significant differences among only one of the twenty-two variables studied. Conclusion: Chinese males have anteriorly long face compare to females.